Oxidized dextran coated magnetic nanoparticles to develop magnetic cross-linked Bacillus lehensis G1 endolevanase aggregates for levan-type fructooligosaccharides synthesis - Hotaf Hassan Makki; Nardiah Rizwana Jaafar; Nashriq Jailani; Zaidah Rahmat; Rosli Md. Illias (PLoS ONE, 2025)
Endolevanase from Bacillus lehensis G1 (rlevblg1) is an enzyme that hydrolyzes levan for the production of levan-type fructooligosaccharides (L-FOS). To maximize the industrial utility of enzymes, it is essential to find effective immobilization techniques that preserve their activity and stability. This study introduced the use of in silico analysis to predict the attachment site in order to perform site-directed cross-linking and develop efficient magnetic cross-linked enzyme aggregates (M-CLEAs). According to the computational analysis, dextran with aldehyde groups has attached far from the active site of rlevblg1 compared to dextran with acetyl functional groups. Oxidized dextran (Odex) was prepared and used to coat the magnetic nanoparticles (MNPs). The coated-MNPs (OdexM) exhibited super-paramagnetic behavior (78.9 emu/g), which was applied to develop M-CLEAs of rlevblg1. The biocatalyst (rlevblg1-OdexM-CLEAs) was easily separated from the reaction medium and acquired a recovered activity of 74.7%, maintaining substrate affinity similar to that of the free enzyme. Moreover, rlevblg1-OdexM-CLEAs exhibited great mechanical stability and potential reusability for 10 cycles with more than 50% recovered activity up to the 5th cycle. The optimum temperature of rlevblg1-OdexM-CLEAs has shifted from 30 to 40 °C resulting in a significant improvement in the thermal stability which was 8.9-fold higher than that of free rlevblg1 after 1 h of incubation at 40 °C. After 8 min of incubation at 45 °C, the activity recovery of free rlevblg1 was completely lost, whereas rlevblg1-OdexM-CLEAs retained almost 20% of its initial activity recovery. In addition to the enhanced operational characteristics, M-CLEAs of rlevblg1 hydrolyzed levan into a high yield of L-FOS, proving the suitability of rlevblg1-OdexM-CLEAs as a biocatalyst for industrial production of L-FOS from levan.